2013
DOI: 10.7717/peerj.151
|View full text |Cite
|
Sign up to set email alerts
|

Typhoon damage on a shallow mesophotic reef in Okinawa, Japan

Abstract: Little is known about effects of large storm systems on mesophotic reefs. This study reports on how Typhoon 17 (Jelawat) affected Ryugu Reef on Okinawa-jima, Japan in September 2012. Benthic communities were surveyed before and after the typhoon using line intercept transect method. Comparison of the benthic assemblages showed highly significant differences in coral coverage at depths of 25–32 m before and after Typhoon 17. A large deep stand of Pachyseris foliosa was apparently less resistant to the storm tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 27 publications
1
40
1
Order By: Relevance
“…Coral community dynamics in Okinawa were different from those in the other case studies, for here, coral cover catastrophically declined in 1998 (Loya et al 2001), and has subsequently been affected by strong typhoons almost every year (Goto et al 2011;White et al 2013). In Okinawa, the density of coral recruits was associated positively with coral cover 1 year before, the density of juvenile corals was associated positively with the density of coral recruits 1 year before, and the reefs were characterised by very low post-settlement success (J : R ,0.01).…”
Section: Discussioncontrasting
confidence: 70%
“…Coral community dynamics in Okinawa were different from those in the other case studies, for here, coral cover catastrophically declined in 1998 (Loya et al 2001), and has subsequently been affected by strong typhoons almost every year (Goto et al 2011;White et al 2013). In Okinawa, the density of coral recruits was associated positively with coral cover 1 year before, the density of juvenile corals was associated positively with the density of coral recruits 1 year before, and the reefs were characterised by very low post-settlement success (J : R ,0.01).…”
Section: Discussioncontrasting
confidence: 70%
“…Coral mortality, generation of rubble, loss of reef structure, erosion of shorelines, creation of new land, or coastal erosion (Maragos et al, 1973;Hagan et al, 2007;Kench et al, 2006;Kench, 2011b;Richmond et al, 2011), localized flooding and salination of crops and freshwater lens, terrestrial runoff, disruption of infrastructure (White et al, 2013).…”
Section: Identifying Hazards and Key Stresses On Coral Reef Systemsmentioning
confidence: 99%
“…In such instances, the time lag for recovery may be many decades and the resultant diversity and abundance of coral cover may shift to a new ecological state (White et al, 2013). In such instances, the time lag for recovery may be many decades and the resultant diversity and abundance of coral cover may shift to a new ecological state (White et al, 2013).…”
Section: Extreme Eventsmentioning
confidence: 99%
“…Despite the high coral diversity found in the Ryukyu Archipelago and the large number of studies on Japanese shallow coral reefs, only a few MCEs have been reported in the upper part of the mesophotic range (between 30 and 55 m; Yamazato, 1972;Kimura et al, 2011;Sinniger et al, 2013;White et al, 2013). Located near relatively densely populated islands, Okinawan reefs are subject to heavy anthropogenic stresses, such as terrestrial runoffs (Hongo and Yamano, 2013) in addition to the strong tropical typhoons that frequently hit this region (Hongo et al, 2012).…”
Section: Introductionmentioning
confidence: 99%